Lived Experiences and Coping Strategies of Unpaid Informal Caregivers of Community-Dwelling Older Adults in Singapore: A Qualitative Systematic Review Protocol - Jonathan Gao; Ze Ling Nai; Woan Shin Tan; Poh Hoon June Teng; Yu Wei Neo; Ee Yuee Chan (International Journal of Qualitative Methods)
Singapore’s population is rapidly ageing, and the city-state is expected to be a super-aged society by 2030. The difficulties and experiences of caregivers of older adults are gaining attention, and various measures to support them have been implemented. Yet, caregivers continue to face challenges ranging from financial difficulties to mental and emotional issues. Qualitative research can provide in-depth understanding on challenges faced by caregivers and how they manage their responsibilities, thus informing both policy and practice. This review aims to synthesize qualitative evidence on the lived experiences and coping strategies of unpaid informal caregivers of community-dwelling older adults in Singapore. A literature search will be conducted on CINAHL, PubMed, PsycINFO, and Web of Science. Relevant websites will also be searched for grey literature. All citations will be screened by two reviewers independently. For included studies, two reviewers will independently: (a) extract data, (b) appraise quality, and (c) assess confidence in review findings. Thematic synthesis will be used to synthesize all included studies. The findings of this review are expected to increase understanding of Singaporean caregivers’ circumstances and highlight implications for interventions and/or policy development.